The vital importance of field trips in the further development of biology education (Genius Repository, 2023)
Field trips play an important role in biology education, providing students with opportunities to interact with the natural world in a hands-on and immersive manner. In this article, we explore the importance of field trips in the study of biology, highlighting the various benefits they bring to the learning experience.